Harmonization of Customary Law and Modern Law: A Study of the Shift in Debt Values in Death Ceremony Traditions in North Toraja Regency - Juwenie, Juwenie; Sumanto, RR Eko Widy Astuty; Tolangi, Edwin; Tandirerun, Asrielg (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The urgency of death ceremonies in North Toraja has significant social and economic dimensions, including in terms of debt. This tradition might involve giving loans in the form of animals. Shifts in this practice, especially in the more modern economic context of settling debts and credits, as well as the influence of the economic system on the traditional customs of the Toraja people. The purpose of this research is to reveal the form of meaning or value shifts in debt and credit that occur during the Rambu Solo death ceremony and to reveal the factors that support the occurrence of meaning or value shifts in the Rambu Solo death ceremony among the Toraja people. The method used in this research is qualitative descriptive research, which emphasizes the use of data obtained from direct interviews with traditional figures and the community in the surrounding area. The research results indicate a shift in values or meaning regarding debt and credit, which is the basis for the implementation of the Death Ceremony (Rambu Solo). The study results suggest that religious figures, educational institutions, and the government should increase guidance to raise awareness among the Toraja people so they abandon behaviors with various motives, especially the motive of displaying prestige, which can lead to debt and credit in order to preserve the authenticity of customs and traditions of death ceremonies (Rambu Solo).